Raven hrupa v delovnem okolju ob upoštevanju različnih poprav - Fras, Vlado (Strojniški vestnik, 2003)
In this paper research are presented that compare the noise levels in the workplace, and consider different correlations (impulse as envisaged by the new Slovenian legislation and tone correction as given in the ISO 9612 standard) or the absence of correctios. The measurements were taken in three metalworking companies. The analysis were performed in determine the influence of a single correction on a worker's daily exposure to noise (especially tone correction, which is not mentioned by the new legislation). The results show a statistically important difference, with a hifh level of reliability between the single corrections.
Keywords: ravni hrupa; poprave tonske; poprave impulzne; analize frekvenčne; delovno okolje; hrup; meritve; frekvenčna analiza